Reasons for replacement and extraction of the subcutaneous implantable cardioverter-defibrillator in a large cohort. (19th May 2022) - Van Der Stuijt, W; Pepplinkhuizen, S; Smeding, L; Olde Nordkamp, LRA; Wilde, AAM; Knops, RE
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The subcutaneous implantable cardioverter-defibrillator (S-ICD) is proven to be a safe and effective alternative to the transvenous ICD. However, battery longevity is estimated to be shorter in the S-ICD, although newer generations S-ICD are thought to have an increased battery longevity compared to the first generation. In addition, the S-ICD lacks the option for pacing therapy and may therefore be extracted in patients who later develop an indication for bradycardia pacing, antitachycardia pacing or resynchronization therapy. In this analysis, we aim to evaluate occurrence and reasons for S-ICD replacement and extraction. Methods: In this retrospective analysis, we collected data on S-ICD generator replacement and extraction from consecutive patients who were implanted with an S-ICD in our tertiary center between February 2009 and December 2021. Results: A total of 408 patients received an S-ICD, with a median follow-up duration of 4.0 (IQR 1.5-6.8) years. Of the 168 implanted first generation S-ICDs, 123 (73.2%) were replaced after a mean of 5.9 ± 0.8 years, all due to battery depletion. A second generation S-ICD was replaced in 2/40 (5%) patients and a third generation S-ICD in 11/200 patients (5.5%), after a mean of 4.8 ± 0.12 and 3.6 ± 1.6 years, respectively. Two third generation S-ICDs were replaced due to device malfunction, all other replacements (134/136, 98.5%) were due to battery depletion. The S-ICD was extracted in 38/408 (9.3%) patients. The mean time from initial implantation to extraction was 3.7 ± 2.5 years. Reasons for extraction were a newly developed indication for pacing or resynchronization therapy (N = 14), an expired indication for ICD therapy (N = 8), heart transplantation or implantation of left ventricular assist device (N = 4), repeated inappropriate shocks (N = 4), pocket infection (N = 3), pocket erosion (N = 2), lead defect (N = 1), Twiddler syndrome (N = 1) and patient preference (N = 1). A new S-ICD could be re-implanted in 7 patients (18.4%), a cardiac resynchronization therapy defibrillator was implanted in 7 patients (18.4%) and there was a need for a transvenous ICD in 10 patients (26.3%). The remaining 14 patients (36.8%) were not re-implanted with any type of ICD. Reasons for end of S-ICD therapy are presented in the figure. Conclusion: In this large cohort, a battery longevity of the first generation S-ICD of 5.9 years was reached. After a median follow-up duration of 4.0 years, 17/408 patients received a transvenous device, due to the need for bradycardia or antitachycardia pacing or resynchronization therapy. Importantly, 14/408 patients underwent an S-ICD extraction and were not re-implanted with any type of ICD. These patients may especially benefit from S-ICD therapy, as this device is less complicated to extract compared to a transvenous ICD.